Reforming the pension system in Lao PDR - Chanthavong, Sisamouth (KDI School, 2011)
The publicly-managed Pay-As-You-Go (PAYG) defined-benefit pension scheme in Lao PDR is described, with an analysis of its financial sustainability in the context of an aging society in a dynamically efficient economy. By using actuarial models developed by the International Labor Organization (ILO), the paper finds that the implicit pension debt (IPD) of the scheme is high in comparison with GDP of the year 2000, the base year for projections. In addition, the paper also evaluates pension system reforms in German, Korea and Thailand. Moreover, regarding the social aspect, a high IPD implies that the burden of maintaining this scheme is borne by the current and future participants. For this reason, the pension scheme in Lao PDR will cause not only financial instability but also inter-generational inequity. In order to avoid this situation, the current scheme needs to be reformed. This paper suggests that the PAYG pension system be reformed to a fullyfunded one. Other considerations include increasing retirement age, solving the implicit pension debt when moving from PAYG to a funded scheme, and the management and regulatory framework of the pension scheme.
Thesis(Master) --KDI School:Master of Public Policy,2011